2017
DOI: 10.24974/amae.11.2.351
|View full text |Cite
|
Sign up to set email alerts
|

Latino Men and their Fathers: Exploring How Community Cultural Wealth Influences their Community College Success

Abstract: Academic scholarship has demonstrated the importance of father engagement in fostering early educational success of their children, but little exploration in this area has focused on the role that fathers play in the college success of their Latino male sons. The purpose of this qualitative study was to understand the role of fathers in the educational success of Latino men attending community colleges. Using community cultural wealth as a lens for this study, the experiences of 130 Latino men at community col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…This study sought to understand the way Latino men described the influence of women in their family on their educational pathways. Similarly, Sáenz, de las Mercédez, Rodriguez, and García‐Louis () utilized the same dataset to explore the ways Latino men perceived their fathers’ influence on their education. Both studies found that parental guidance, namely consejos , served as motivation and instilled resilience for Latino men.…”
Section: The Role Of Family For Latino Men In Community Collegementioning
confidence: 99%
See 1 more Smart Citation
“…This study sought to understand the way Latino men described the influence of women in their family on their educational pathways. Similarly, Sáenz, de las Mercédez, Rodriguez, and García‐Louis () utilized the same dataset to explore the ways Latino men perceived their fathers’ influence on their education. Both studies found that parental guidance, namely consejos , served as motivation and instilled resilience for Latino men.…”
Section: The Role Of Family For Latino Men In Community Collegementioning
confidence: 99%
“…On one hand, earning a college degree inspired a sense of pride, not only for Latino men, but also for the entire family. Yet, the weight of choosing a career path with a stronger earning potential to benefit the entire family further complicates the internalized pressure Latino men experienced due to expected gender roles (i.e., breadwinner) (Sáenz et al., ; Sáenz, Bukoski, Lu, & Rodriguez, ). Latino men must often negotiate conflicting messages, particularly from their fathers, about time spent toward education (e.g., studying, attending class) versus working to contribute financially to their family.…”
Section: The Role Of Family For Latino Men In Community Collegementioning
confidence: 99%
“…Scholars have attempted to shift away from deficit‐based narratives by centering the assets Latinx and underserved students from low‐income backgrounds possess by applying and broadening Yosso's framework (Crisp, Doran, Carales, & Potts, ; Pérez Huber, ; Kouyoumdjian, Guzman, Garcia, & Talavera‐Bustillos, ; Luna & Martinez, ; Rendón et al., ). Yosso's framework has also been foundational in the study and advancement of a more accurate characterization of the experiences of Latinx community college students (Crisp et al., ; Sáenz, de las Mercédez, Rodriguez, & García‐Louis, ; Sáenz, Garcia‐Louis, de las Mercédez, & Rodriguez, ). Building from Community Cultural Wealth, Rendón et al.…”
Section: Theoretical Framework Grounded In Strength‐based Thinkingmentioning
confidence: 99%
“…Though the Latino/a/x population continues to increase in the United States, literature on the experiences of Latino males in community colleges remains scarce (Harris & Wood, 2013). Within the research that does exist on Latino male community college students, there has been a focus on a range of topics including students' mentoring experiences (Torrens, Salinas, & Floyd, 2017); the role of family in helping students navigate the community college (Sáenz, Garcia-Louis, Peterson Drake, & Guida, 2018); student interactions with faculty and staff (Rodriguez, Massey, & Sáenz, 2016); financial literacy (Salinas & Hidrowoh, 2018); expressions of masculinity (Vasquez-Urias & Wood, 2015); and Latino males' relationships with their fathers (Sáenz, de Las Mercédez, Rodriguez, & García-Louis, 2017). Others have focused on institutional level and state factors that promote success for Men of Color (Rodriguez, Garbee, Miller, & Saenz, 2017;Salinas & Friedel, 2016;Vasquez-Urias, 2012).…”
Section: Experiences Of Latino Men In Community Collegesmentioning
confidence: 99%